Effect of compost tea and diluted sea water on growth, yield, and chlorophyll content of Pak Choi (Brassica rapa L.) - Arianti Dwi Mawarti; Slamet Supriyadi; Catur Wasonowati (Agrovigor, 2026)
A combination of Diluted Sea Water (DSW) and Aerated Compost Tea (ACT), as a nutrient source, may increase yield of Pak Choi (Brassica rapa L.). The study investigating  the interaction effects of DSW and ACT on growth and yield of Pak Choi was conducted at the greenhouse of Trunodjoyo University Madura from December 2022 – January 2023. This factorial experiment was arranged on a completely randomized design with two factors. The DSW factor consisted of two levels: S0 (0% ) and S1 (3,0%). The ACT factor contained three levels: P0 (0%), P1 (6,0%), and P2 (12,0%). The combination resulted in six treatments: S0P0 (Control), S0P1 (6% ACT), S0P2  (12% ACT), S1P0 (3% DSW), S1P1 (3% DSW + 6% ACT), and S1P2 (3% DSW + 12% ACT). Each treatment was replicated for four times, totaling 24 experimental units. Data were analyzed using ANOVA (p 0.05) and mean differences were analyzed by DMRT (p 0.05). Results showed that interaction of DSW and ACT significantly increased plant height, leaf number, leaf area, fresh  and dry weight, and chlorophyll content with the S1P2 treatment yielding the best result. Plant yield and chlorophyll content under S1P2 was respectively 25% and 19% higher than the control. Effects of higher concentration of  DSW and ACT on plant growth and yield as well as the changes of soil characteristics warrant for further study.